Identification of Shared Genes Between Ischemic Stroke and Parkinson's Disease Using Genome-Wide Association Studies - Lang, Wenjing; Wang, Junjie; Ma, Xiaofeng; Zhang, Nong; Li, He; Cui, Pan; Hao, Junwei (Frontiers in Neurology, 2019)
Ischemic stroke (IS) and Parkinson’s disease (PD) are two neurological diseases that often strike individuals of advanced age. Although thought of as a disease of old age, PD can occur in younger patients. In many of these cases, genetic mutations underlie the disease. As with PD, stroke can also have a genetic component. Although many of the risk factors for IS are considered to be modifiable, a significant portion is not, suggesting that some of stroke risk factors may have a genetic origin. Large-scale genome-wide association studies (GWAS) have identified several IS and PD gene variants recently. Converging epidemiologic and pathological evidence suggests that IS and PD may be linked. However, it is still unclear whether these two conditions share a common mechanism. Here, we sought to determine the genetic mechanism underlying the possible association between IS and PD. We conducted a multi-step systemic analysis comprising (1) identification of IS and PD variants validated by known GWAS, (2) two separate gene-based tests using VErsatile Gene-based Association Study 2 (VEGAS2) and PLINK, (3) a transcriptome-wide association study (TWAS), and (3) analyses of gene expression using an online tool in Gene Expression Omnibus. Our investigation revealed that IS and PD have in common five shared genes: GPX7, LBH, ZCCHC10, DENND2A, and NUDT14, which pass gene-based tests. Functionally, these genes are expressed differentially in IS and PD patients compared to neurologically healthy control subjects. This genetic overlap may provide clues on how IS and PD are linked mechanistically. This new genetic insight into these two diseases may be very valuable for narrowing the focus of future studies on the genetic basis of IS and PD and for developing novel therapies.